Linguistic and Cultural Education for Bildung and Citizenship - BYRAM, MICHAEL (The Modern language journal (Boulder, Colo.), 2010)
At the heart of theory and practice in foreign language teaching, as of education in general, is the need to clarify purposes. Given the number of books and articles on methods and techniques for the classroom, it might appear that it is methodology that is central. The dominant contemporary assumption is that the purpose of foreign language teaching is to develop communicative competence and discussion turns around "communicative methodology" in its various forms, but methodology is a second-order issue derived from the question of purposes. Here, Byram focuses on purposes--avoiding the narrowness of the terms "aims and objectives"--and suggests that a reappraisal of purposes with respect to the cultural dimension of foreign language teaching will lead to richer, more complex outcomes.